The Gateway to Computer Science Excellence
First time here? Checkout the FAQ!
x
0 votes
81 views

asked in Linear Algebra by Junior (673 points)
edited by | 81 views
0
Is answer B?
0
Solution?
0
There are two ways:-

If base cases given then simply apply values: a0 = 0

Substitute n value =  0 , Now only second option holds good 2^0 - 1 = 1-1 = 0.

next method:-

Solving using linear homogeneous method. first form equation and then find the roots , apply the roots and create the recurrence equation.

This might be time consuming . there are several videos available in youtube
0
any solution?

1 Answer

0 votes
Substituting x^2 for an+2, x ^1 for an+1 and x^0 for an,we get the equation,

           x^2 -3x + 2 =0

           roots of the above equation are 1,2

          Therefore,characteristic equation will be,

          an=c1(1)^n + c2(2)^n   where c1,c2 are constants;

          Substituting the value of n=0 and n=1,we get c1=-1 and c2=1;

          Therefore, an=2^n-1

                   Hence (b)
answered by (159 points)

Related questions

Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
49,541 questions
54,084 answers
187,213 comments
70,992 users